Christian Religious Education Strategies for Early Childhood in Fostering Knowledge of God in Schools - Ruthnawaty Setiawan; Dunant Frederick Saukotta; Margreth Luciyanna Risakotta; Yusak Tanasyah (Journal of Religious and Socio-Cultural, 2023)
This study aims to identify and analyze Christian religious education strategies that are effective in fostering knowledge of God in early childhood. Early childhood is a critical phase of development in which the foundations of character and moral values are formed. Christian religious education at this stage is considered an important factor in shaping a child's understanding of the existence of God. This study explores effective strategies of Christian religious education targeted at early childhood, with an emphasis on instilling a deep understanding of God. The aim is to provide practical insights and guidance for educators and stakeholders investing in the spiritual development of young learners. This research uses a qualitative approach with literature research methods. Recognizing the formative nature of early experiences, the focus is on creating an environment that encourages spiritual growth, instills Christian values, and fosters a personal relationship with God. This exploration advocates the integration of age-appropriate methods, engaging activities, and supportive communities to build a strong foundation for the development of a child's understanding of God in the school environment.